PERSEPSI WIRAUSAHA MUDA DALAM MENINGKATKAN PRODUKTIVITAS DI TENGAH PERSAINGAN PASAR - Khaeruman, Khaeruman; Tabroni, Tabroni; Hanafiah, Hafidz; Dewi, Irma Nurmala (Yayasan Education and Social Center, 2025)
This study aims to understand young entrepreneurs’ perceptions in enhancing productivity amidst market competition in Serang City, Banten Province. A qualitative approach was employed using in-depth interviews with several young entrepreneurs from various business sectors. The findings reveal that productivity is perceived adaptively as a synergy between creativity, efficiency, and innovation in responding to market changes. Digital technology plays a crucial role in expanding market access and improving operational effectiveness. Entrepreneurial motivation serves as an essential internal factor for business sustainability, while managerial limitations and limited access to capital remain significant challenges. The study highlights the importance of policy support, practice-based training, and collaboration among government, academia, and the private sector to build a productive and sustainable youth entrepreneurship ecosystem.